An investigation of the educational aspirations of high school female learners - Willemse, Anneley (Rhodes University, Faculty of Education, Department of Education, 2008)
Researchers hold numerous perceptions of the educational aspirations and future career choices of teenage girls. Studies argue that factors such as the curriculum, teachers' and parents' attitudes, the impact of HIV/AIDS, and teenage pregnancy, influence girls' future educational and occupational hopes and dreams either positively or negatively. Other researchers claim that learners' career choice is limited by their potential and school performance. The existing literature also suggests that girls have lower self-esteem and levels of achievement than boys. This research seeks to gain insight into high school girls' perceived academic and vocational prospects. The research was carried out in an interpretive paradigm. Six secondary school female learners from one school participated in the study. Semistructured interviews were the core method of data collection, supplemented by questionnaires and a focus group interview. As teenagers, the girls were expected to already have started to think about their future hopes and dreams. The findings revealed that all the girls seemed to experience school as a place where they could acquire knowledge about what they needed to make them autonomous and successful in adult life. For them, their parents remained their major significant others. They regarded fear of poverty as a major factor motivating them to achieve their educational and vocational aspirations. Peer pressure appeared not to be a major determinant of these girls' successes in school. The girls believed that there is a relationship between their academic performance and their future vocational choice. In addition, the girls did not see boys as a threat to their climbing the ladder of success.
Keywords: Women -- Education; Student aspirations; Vocational interests; High school students; Sex discrimination in education; Sex differences in education; Teenage girls -- Education